ผลกระทบของกรดไขมันทรานส์ในอาหารต่อการเกิดโรคหัวใจและหลอดเลือด (IMPACT OF TRANS FATTY ACID ON CARDIOVASCULAR DISEASE) - ชายเกตุ, สิริมนต์; หาญรุ่งโรจน์, ตลับพร (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2010)
กรดไขมันทรานส์ผลิตในอุตสาหกรรมอาหาร โดยการเติมไฮโดรเจนลงในน้ำมันพืช ทำให้ได้ไขมันที่มีสถานะเป็นของแข็งเพิ่มขึ้น ซึ่งจะเพิ่มอายุการเก็บและความคงทนของผลิตภัณฑ์ บริษัทอาหารหลายแห่งใช้กรดไขมันทรานส์เนื่องจากมีราคาถูกและใช้ได้ง่าย นอกจากนี้ร้านอาหารและร้านอาหารจานด่วนหลายแห่งใช้กรดไขมันทรานส์ในการทอดอาหารแบบน้ำมันท่วม เนื่องจากสามารถใช้น้ำมันนี้ในการทอดได้หลายๆ ครั้ง เราสามารถพบไขมันทรานส์ในอาหารหลายชนิด เช่น น้ำมันพืชที่ผ่านการเติมไฮโดรเจน มาการีนชนิดแท่ง แครกเกอร์ คุกกี้ ขนมขบเคี้ยว อาหารทอด และผลิตภัณฑ์ขนมอบ ไขมันทรานส์มีผลกระทบต่อสุขภาพโดยเพิ่ม LDL-C และลด HDL-C ซึ่งเป็นปัจจัยเสี่ยงต่อการเกิดโรคหัวใจและหลอดเลือด ปัจจุบันประเทศไทยยังไม่มีกฎหมายบังคับให้มีการระบุปริมาณกรดไขมันทรานส์ลงในฉลากโภชนาการ ผู้บริโภคสามารถสังเกตดูที่ส่วนประกอบของอาหารบนบรรจุภัณฑ์อาหารว่ามีคำว่า trans fats หรือ partially hydrogenated หรือ shortening หรือไม่ ถ้ามีแสดงว่าอาหารนั้นมีกรดไขมันทรานส์เป็นส่วนประกอบ Keywords: Trans fatty acid, Cardiovascular disease, Hydrogenation, Shortening Trans fats is produced in industrial foods by so called process hydrogenation, for the purpose to harden the fats providing specific properties to gain higher stability and longer shelf life. Many food manufacturers make good use of trans fat for their inexpensive cost and facility. Several restaurants, especially fast foods business use trans fats for deep-frying technique due to the reason of many times reuses. Trans fats are found in many kinds of processed foods such as vegetable shortenings, hard margarines, crackers, cookies, snack foods and baked products. Trans fats has adverse effect on health, not only by raising bad cholesterol or LDL-cholesterol, similar to saturated fats and other cholesterol diets but also by lowering good cholesterol or HDL-cholesterol, resulting in higher risk for coronary heart disease. At the present time, Thailand has no legislation on nutrition facts label of trans fats. The consumers can check the ingredients of food products on the packages on which "trans fats", "hydrogenated" or shortening" are shown. That indicated such food products contain trans fats. Keywords: Trans fatty acid, Cardiovascular disease, Hydrogenation, Shortening